Balance of Payments Statistics Yearbook, 1999. (Balance of Payments Statistics; Balance of Payments Statistics ;, 1999)
The BOPS Yearbook, usually published in December, contains balance of payments statistics for most of the world, compiled in accordance with the IMF's Balance of Payments Manual. Part 1 includes aggregate as well as detailed information in the form of analytical and standard component presentations for countries. Part 2 provides tables of data, featuring area and world totals of balance of payments components and aggregates. Part 3 presents descriptions of methodologies, compilation practices, and data sources used by individual member countries in compiling their balance of payments and international investment position statistics.